Isolation and Characterization of Bacillus Consortia for Plant Growth Promotion in Rice (Oryza sativa L.) - Modi, Krunal; Jha, Sanjay; Patel, Pathik; Suthar, Harish (Plantae Scientia, 2022)
In this study, soil samples from the rhizosphere of various uncultivated weeds were collected from fifteen different locations of Gujarat. Heat treatment was given at 65°C for 20 minutes prior to initial screening for spore-forming Bacillus spp. Among them, 20 nitrogen-fixing (NFB), 27 phosphate solubilising (PSB) and 15 potassium mobilizing (KMB) isolates were screened primarily. After molecular identification only Bacillus isolates were further selected and characterized. Three superior Bacillus isolates were selected from each category by secondary screening. All isolates belonging to different category were compatible in nature and showed significant ammonia production, ARA, phosphate solubilisation, potassium mobilization, siderophore production, IAA production and organic acid producers. The relative expression analysis of three genes NRT2.1 (Nitrate transporter), PT6 (Phosphorus transporter), and AKT1 (Potassium transporter) at transcriptional level were performed in the juvenile root tissues of Rice using qRT-PCR technique at 15th, 30th and 45th days after transplanting with Actin as a internal control. Rice transplants were inoculated with different NPK fixing Bacillus consortia, which significantly improved growth parameters as compared to control in field study. Various growth and yield attributing characters of rice viz., plant height (at 60 DAT, 90 DAT, and at harvesting), number of productive tillers, days to 50 % flowering, 100 seed weight, grain yield, straw yield, as well as dry biomass per hectare were significantly influenced by different treatments. An application of 100 % RDF with NPK consortia (T7) treatment of rice crop resulted in significantly higher plant height (49.25 cm at 60 DAT, 107.00 cm at 90 DAT, 129.50 cm at harvesting), days to 50% flowering (75.63), 100 seed weight (3.53 g), number of productive tillers per plant (12.13), grain yield (6889.00 kg ha-1), straw yield (8754.25 kg ha-1) and dry biomass (7889.25 kg ha-1) followed by the treatments T4 (T2 + N consortia), T5 (T2 + P consortia), T6 (T2 + K consortia), and T2 (RDF (NP) 100%). Nutrient content in grain and straw was differing significantly due to different treatments. However, significantly higher N, P, K, content in straw (1.28 %, 0.15 %, and 1.52 %) and grain (2.06 %, 0.23 %, and 0.25 %) respectively, were recorded under the treatment T7. The spore forming Bacillus consortia was able to survive at a wide range of temperature and pH fluctuations and found to be effective as N-fixers, P-solubilizers, K-mobilizers, siderophore producers, IAA producers with having antagonistic activity against rice pathogen Magnaportha oryzae.